2018
DOI: 10.1186/s13075-018-1649-1
|View full text |Cite
|
Sign up to set email alerts
|

The plasma biomarker soluble SIGLEC-1 is associated with the type I interferon transcriptional signature, ethnic background and renal disease in systemic lupus erythematosus

Abstract: BackgroundThe molecular heterogeneity of autoimmune and inflammatory diseases has been one of the main obstacles to the development of safe and specific therapeutic options. Here, we evaluated the diagnostic and clinical value of a robust, inexpensive, immunoassay detecting the circulating soluble form of the monocyte-specific surface receptor sialic acid binding Ig-like lectin 1 (sSIGLEC-1).MethodsWe developed an immunoassay to measure sSIGLEC-1 in small volumes of plasma/serum from systemic lupus erythematos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 35 publications
3
48
0
1
Order By: Relevance
“…Recently, we have reported that the plasma concentration of the soluble form of the adhesion receptor SIGLEC-1 (sSIGLEC-1) is sensitive marker of the type I IFN transcriptional signature (27). In addition, we have shown that the concentration of sSIGLEC-1 was also associated with increased disease activity in SLE patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have reported that the plasma concentration of the soluble form of the adhesion receptor SIGLEC-1 (sSIGLEC-1) is sensitive marker of the type I IFN transcriptional signature (27). In addition, we have shown that the concentration of sSIGLEC-1 was also associated with increased disease activity in SLE patients.…”
Section: Resultsmentioning
confidence: 99%
“…Soluble SIGLEC-1 (sSIGLEC-1) concentrations were measured in plasma samples from all study participants using a time-resolved fluorescence immunoassay, as described previously (27).…”
Section: Methodsmentioning
confidence: 99%
“…Macrophages regulate the autoimmune system by modulating multiple pathways, not just through TNF expression and phagocytic activity. Abnormal expression of monocyte-surface markers, such as FcγRIII, CD40, CD244, CR4, Siglec-1, and Siglec-4, have been reported in monocytes from patients with SLE [62,64,65,66]; therefore, dysregulation of monocyte surface molecules could skew optimal immune responses, including pathogenic cytokine and chemokine expression [62].…”
Section: Discussionmentioning
confidence: 99%
“…However, an IFN score was recently shown to predict the development of SLE in at-risk individuals 32. Alternative biomarkers of type I IFN activity have been evaluated and include the IFN-α response protein, sialic acid-binding Ig-like lectin 1, which is expressed exclusively on tissue-resident monocyte-derived dendritic cells and tissue-resident macrophages 33. Other gene signatures, such as plasmablast and neutrophil signatures, may correlate better with SLE disease activity than the IFNGS at the individual level 31…”
Section: Type I Ifns In Autoimmune Diseasesmentioning
confidence: 99%